Pelatihan Software Publish or Perish, Vosviewer, dan Mendeley Untuk Meningkatkan Keterampilan Menulis Karya Ilmiah Ikatan Mahasiswa Tegal - Muhammad Ulil Azmi; Fateh Rizky Ramadhani; Alfiati Ruba’atin; Fatmawati, Windy (Sekolah Tinggi Teknologi Industri (STTI) Bontang, 2023)
Students still think writing scientific papers is difficult. However, writing scientific papers is a form of implementing the tri dharma of higher education. This then requires students to write starting from small, close, and simple things. Writing support software training is something useful. Technology is a means of supporting the writing of scientific papers for researchers who are technologically literate. The application software used in the training will make it easier for students to analyze what needs to be researched, what previous research looks like, writing updates, and much more. This service activity consists of three stages, namely preparation, implementation and evaluation. Each stage is carried out sequentially and continuously. Writing skills are combined with technology and passed on to fellow students so they can contribute to change.